Hymnen - Stockhausen, Karlheinz 1928-2007 (Kürten Stockhausen Verlag, 1995)
HYMNEN Electronic and Concrete MusicHYMNEN electronic and concrete Music with soloists (Aloys Kontarsky, Alfred Alings,Rolf Gehlhaar, Johannes G. Fritsch, Harald Bojé, K. Stockhausen) (4 CDs)